Quantitative analysis of palm carotene using fourier transform infrared and near infrared spectroscopy - Moh, M. H.; Che Man, Y. B.; Badlishah, B. S.; S., Jinap; Saad, M. S.; Abdullah, W. J. W. (Wiley, 1999)
β‐Carotene content is usually determined by using ultraviolet (UV)‐visible spectrophotometry at 446 nm. In this study, two spectroscopic techniques, namely, Fourier transform infrared (FTIR) and near infrared (NIR) spectroscopy, have been investigated and compared to UV‐visible spectrophotometry to measure the β‐carotene content of crude palm oil (CPO). Calibration curves ranging from 200 to 800 ppm were prepared by extracting β‐carotene from original CPO using open‐column chromatography. Separate partial least squares calibration models were developed for predicting β‐carotene based on the spectral region from 976 to 926 cm−1 for FTIR spectroscopy and 546 to 819 nm for NIR spectroscopy. The correlation coefficient ( R 2) and standard error of calibration obtained were 0.972 and 25.2 for FTIR and 0.952 and 23.6 for NIR techniques, respectively. The validation set gave R 2 of 0.951 with standard error of performance (SEP) of 25.78 for FTIR technique and R 2 of 0.979 with SEP of 19.96 for NIR technique. The overall reproducibility and accuracy did not give comparable results to that of spectrophotometric method; however, the standard deviation of prediction was still within ±5% β‐carotene content over the range tested. Because of their rapidness and simplicity, both FTIR and NIR techniques provide alternative means of measuring β‐carotene content in CPO. In addition, these two spectroscopic techniques are environmentally friendly since no solvent is involved.